DNA repair in trinucleotide repeat ataxias. (10th September 2018) - Yau, Wai Yan; O'Connor, Emer; Sullivan, Roisin; Akijian, Layan; Wood, Nicholas W.
Abstract : The inherited cerebellar ataxias comprise of a genetic heterogeneous group of disorders. Pathogenic expansions of cytosine–adenine–guanine (CAG) encoding polyglutamine tracts account for the largest proportion of autosomal dominant cerebellar ataxias, while GAA expansion in the first introns of frataxin gene is the commonest cause of autosomal recessive cerebellar ataxias. Currently, there is no available treatment to alter the disease trajectory, with devastating consequences for affected individuals. Inter‐ and Intrafamily phenotypic variability suggest the existence of genetic modifiers, which may become targets amendable to treatment. Recent studies have demonstrated the importance of DNA repair pathways in modifying spinocerebellar ataxia with CAG repeat expansions. In this review, we discuss the mechanisms in which DNA repair pathways, epigenetics and other genetic factors may act as modifiers in cerebellar ataxias due to trinucleotide repeat expansions. Abstract : Alterations in different DNA repair pathways, epigenetics and other genetic factors are associated with variations in the age of onset in inherited ataxias with cytosine–adenine–guainine (CAG) repeat expansions. In particular, mutated DNA repair genes may lead to further expansions of somatic CAG tract in postmitotic neurons and subsequent neurodegeneration.